Rare bacterial biosphere is more environmental controlled and deterministically governed than abundant one in sediment of thermokarst lakes across the Qinghai-Tibet Plateau - Ren, Ze; Luo, Wei; Zhang, Cheng (Frontiers in Microbiology, 2022)
Thermokarst lakes are widely distributed in cold regions as a result of ice-rich permafrost thaw. Disentangling the biogeography of abundant and rare microbes is essential to understand the environmental influences, assembly mechanisms, and responses to climate change of bacterial communities in thermokarst lakes. In light of this, we assessed the abundant and rare bacterial subcommunities in sediments from thermokarst lakes across the Qinghai-Tibet Plateau (QTP). The OTU richness was more strongly associated with location and climate factors for abundant subcommunities, while more strongly to physicochemical variables for rare subcommunities. The relative abundance of abundant and rare taxa showed opposite patterns with abundant taxa having greater relative abundance at higher latitude and pH but at lower mean annual precipitation and nutrients. Both abundant and rare subcommunities had a clear distribution pattern along the gradient of latitude and mean annual precipitation. Abundant subcommunities were dominantly shaped by dispersal limitation processes (80.9%), while rare subcommunities were shaped almost equally by deterministic (47.3%) and stochastic (52.7%) processes. The balance between stochastic and deterministic processes was strongly environmentally adjusted for rare subcommunities, while not associated with environmental changes for abundant subcommunities. The results shed light on biogeography patterns and structuring mechanisms of bacterial communities in thermokarst lakes, improving our ability to predict the influences of future climate change on these lakes.